Debate over gay rights. - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows gays, lesbians and their straight supporters crowded into a Monterey Savings and Loan conference room to hear a historic debate on gay rights between Assemblyman Art Agnos and Pastor Charles McIlhenny.